Pharmacokinetics and bioavailability of tuftsin-derived T peptide, a promising antitumor agent, in beagles. Issue 1 (February 2016) - Gu, Ruolan; He, Yanlin; Han, Su; Yuan, Shoujun; An, Yinghong; Meng, Zhiyun; Zhu, Xiaoxia; Gan, Hui; Wu, Zhuona; Li, Jian; Zheng, Ying; Zhang, Ling; et al.
Abstract: Tuftsin, a natural phagocytosis-stimulating tetrapeptide, had aroused much interest in tumor immunotherapy, but the poor pharmacokinetics hampered its clinical developments, for that it was extremely susceptible to degradation by enzymolysis in vivo . T Peptide (TP) was a newly designed tuftsin derivative aimed to enhance stability and was proved to have significant antitumor activity. In this study, the pharmacokinetics and bioavailability of TP was first clarified in beagles with subcutaneous administration, by using a simple and robust competitive ELISA method. Dose-dependency and non-linear dynamics of TP after single-dose (2, 6 and 18 mg kg −1, respectively) were found, and the half-time of TP was proved to reach 1.3–2.8 h. Multiple dosing of 6 mg kg −1 once a day for 7 days resulted in a slight accumulation (accumulation index was 1.92 ± 0.43), indicating that the dosing interval in the following clinical trial needs to be extended. The absolute bioavailability of TP was 31.1 ± 6.2% after subcutaneous administration. These results first demonstrated the pharmacokinetics and bioavailability data of TP in vivo, which illustrated the potential druggability of TP and provided useful information for the dosage regimen design in the following clinical trials, as well as a simple and feasible analytical method for clinical sample analysis.